Sex-specific microbiota associations with backfat thickness, eye muscle area, and rumen fermentation in Qinchuan cattle - Yueting Pan; Gege Sun; Guo Li; Shuaicheng Chen; Haibing Liu; Huaxuan Li; Chugang Mei; Wucai Yang; Linsen Zan (BMC Microbiology)
Abstract Background Ruminant livestock are essential for global food production, and understanding sex-specific rumen fermentation and microbial differences is key to improving production efficiency and meat quality. This study explored sex-specific variations in backfat thickness, eye muscle area, rumen fermentation, and microbiota in Qinchuan cattle. Results The results revealed that heifers exhibited higher backfat thickness, butyrate concentrations, and acetate/propionate ratio, whereas bulls had larger eye muscle areas and higher propionate concentrations. Volatile fatty acids (VFAs) transport-related genes (CA4, DRA, and NHE1) were more highly expressed in bulls. Heifers showed greater microbial diversity with distinct sex-specific community structures. Bulls had a higher abundance of Prevotella, while butyrate-producing bacteria like Butyrivibrio and Pseudobutyrivibrio were more abundant in heifers. Functional predictions revealed that bulls were enriched in glycan biosynthesis and amino acid metabolism pathways, whereas heifers showed enhanced lipid metabolism pathways. Correlation analyses showed that backfat thickness was positively correlated with acetate and butyrate production, and acetate/propionate ratio, but negatively correlated with Veillonellaceae_UCG-001. Eye muscle area was negatively correlated with isobutyrate production and the abundance of Elusimicrobium and Anaeroplasma, but positively correlated with Lachnospiraceae_NK3A20_group. Redundancy analysis (RDA) identified propionate and butyrate as key drivers of microbial community differences. The Random Forest model identified key predictors for backfat thickness, including rumen fermentation parameters, microbial taxa, and metabolic pathways, explaining 28% of the variation. However, eye muscle area was not well predicted by the current parameters. Conclusion These findings enhance our understanding of sex-specific microbial and metabolic profiles, offering potential strategies for optimizing livestock management and breeding programs. Graphical Abstract